The Influence of Intellectual Capital on Financial Performance - Melania Fitri Ariyanti; Zahroh Naimah (Eduvest - Journal of Universal Studies, 2025)
This study examines the impact of intellectual capital components on the financial performance of banking institutions in Indonesia. Using multiple regression analysis on 149 bank-year observations from 2019 to 2023, we investigate the influence of human capital efficiency (HCE), structural capital efficiency (SCE), capital employed efficiency (CEE), and technological capital efficiency (TCE) on bank performance, as measured by return on assets (ROA). The findings reveal that human capital (β = 0.005, p < 0.001) and capital employed (β = 0.012, p < 0.05) significantly enhance financial performance, while structural capital (β = -0.007, p < 0.001) exhibits a significant negative effect. Notably, technological capital shows no significant impact on bank performance (p > 0.05). The model explains 79.8% of the variance in financial performance (Adjusted R² = 0.798). These results suggest that Indonesian banks rely more heavily on tangible capital and human resources than on structural and technological investments for profitability enhancement.